Dimerization of GPCRs: Novel insight into the role of FLNA and SSAs regulating SST2 and SST5 homo- and hetero-dimer formation - Treppiedi, Donatella; Marra, Giusy; Di Muro, Genesio; Catalano, Rosa; Mangili, Federica; Esposito, Emanuela; Calebiro, Davide; Arosio, Maura; Peverelli, Erika; Mantovani, Giovanna (Frontiers in Endocrinology, 2022)
The process of GPCR dimerization can have profound effects on GPCR activation, signalling and intracellular trafficking. Somatostatin receptors (SSTs) are class A GPCRs abundantly expressed in pituitary tumors where they represent the main pharmacological targets of somatostatin analogs (SSAs) thanks to their antisecretory and antiproliferative actions. The cytoskeletal protein filamin A (FLNA) directly interacts with both somatostatin receptor type 2 (SST2) and 5 (SST5) and regulates their expression and signalling in pituitary tumoral cells. So far, the existence and physiological relevance of SSTs homo- and hetero-dimerization in the pituitary have not been explored. Moreover, whether octreotide or pasireotide may play modulatory effects and whether FLNA may participate to this level of receptor organization have remained elusive. Here, we used a Proximity Ligation Assay (PLA)–based approach for the in situ visualization and quantification of SST2/SST5 dimerization in rat GH3 as well as in human melanoma cells either expressing (A7) or lacking (M2) FLNA. First, we observed the formation of endogenous SST5 homo-dimers in GH3, A7 and M2 cells. Using the PLA approach combined with epitope tagging, we detected homo-dimers of human SST2 in GH3, A7 and M2 cells transiently co-expressing HA- and SNAP-tagged SST2. SST2 and SST5 can also form endogenous hetero-dimers in these cells. Interestingly, FLNA absence reduced the basal number of hetero-dimers (-36.8±6.3% reduction of PLA events in M2, P<0.05 vs A7), and octreotide but not pasireotide promoted hetero-dimerization in both A7 and M2 (+20.0 ±11.8% and +44.1±16.3% increase of PLA events in A7 and M2, respectively, P<0.05 vs basal). Finally, immunofluorescence data showed that SST2 and SST5 recruitment at the plasma membrane and internalization are similarly induced by octreotide and pasireotide in GH3 and A7 cells. On the contrary, in M2 cells, octreotide failed to internalize both receptors whereas pasireotide promoted robust receptors internalization at shorter times than in A7 cells. In conclusion, we demonstrated that in GH3 cells SST2 and SST5 can form both homo- and hetero-dimers and that FLNA plays a role in the formation of SST2/SST5 hetero-dimers. Moreover, we showed that FLNA regulates SST2 and SST5 intracellular trafficking induced by octreotide and pasireotide.